Ginkgolide B for Myocardial Ischemia/Reperfusion Injury: A Preclinical Systematic Review and Meta-Analysis - Zhu, Peng-Chong; Tong, Qiang; Zhuang, Zhuang; Wang, Zi-Hao; Deng, Li-Hui; Zheng, Guo-qing; Wang, Yan (Frontiers in Physiology, 2019)
Ginkgolide B (GB) is an extract of dried Ginkgo biloba leaves and possesses various pharmacological activities in the cardiovascular system. Herein, we aim to assess the available preclinical evidence and possible mechanisms of GB for myocardial ischemia/reperfusion injury. The study quality score was assessed using the CAMARADES 10-item checklist. Rev-Man 5.3 software was used for data analyses. Nineteen studies with total 437 animals were included for analysis. Meta-analyses indicated that GB interventions significantly reduce myocardial infarct size and cardiac markers when compared with control (P< 0.05). The possible mechanisms via which GB exerts cardioprotective effects are mainly associated with anti-oxidation, anti-inflammation, anti-apoptosis, and improvement of energy metabolism. Our study indicates that GB might be a promising cardioprotective agent for myocardial ischemia/reperfusion injury and may contribute to future clinical trial design.